Demographic factors associated with loss to follow up in the management of chronic otitis media: case–control study. Issue 2 (18th December 2015) - Nash, R; Fox, R; Srinivasan, R; Majithia, A; Singh, A
Abstract: Objective: The likelihood of a patient attending regular follow up can affect decision making when planning and performing tympanomastoid surgery. This study investigated whether demographic factors were associated with loss to follow up. Methods: A database of patients who had been investigated and treated for chronic otitis media was searched. Patients lost to follow up and a matching sample of patients who were formally discharged were identified. The demographic factors of age, sex and postcode were compared between the two groups. The information collected was also used to provide measures of deprivation. Results: Fifty patients in each group were identified. Patients lost to follow up were significantly younger than patients formally discharged ( p < 0.02), and were more likely to live in an area of education and training deprivation ( p < 0.05). Conclusion: Younger patient age, and living in an area of education and training deprivation, are associated with a higher incidence of loss to follow up.